Negative Early Reproductive Health Decisions and Associated Outcomes Among Women in the Northern Region of Ghana - Iddrisu, M.R. (University of Ghana, 2019)
Background: A growing body of demographic and sociological literature indicates that early life decisions and choices individuals make have important health consequences in later life Within reproductive health in particular, a number of studies suggest that early reproductive health decisions that women make have an impact on their reproductive health outcomes in later life. Despite this growing evidence, little understanding exists in Ghana about the relationship between negative early reproductive health decisions of women and later life reproductive health outcomes. Based on a life course perspective, this study aimed to examine the early reproductive health decisions of women and their associated reproductive health outcomes in the northern region of Ghana. Methods: A concurrent mixed methods retrospective study design was conducted to elicit information from married women within the ages of 15-49 years as well as other key informants. Systematic sampling was used to sample a total of 390 married women to take part in the survey. A combination of purposive and snowball sampling was used to select 40 key informants and a total of 130 women between ages 15- 49 with a minimum marriage experience of five years to take part in qualitative focus group discussions, in-depth interviews and key informant interviews. Quantitative data were collected through a face-face interview using structured questionnaires. Qualitative data were collected through focus group discussions, in-depth interviews and key informant interviews using unstructured topic/discussion guides. Descriptive statistical methods were used to describe important characteristics of survey respondents. Bivariate and multivariate logistic regression analyses were performed to examine association between early reproductive health decisions and reproductive health outcomes in later life. Confidence level and statistical significance were set at 95% and a p-value<0.05 respectively. Stata 13 version software was used in the analysis of the quantitative data. Qualitative interviews were audio-recorded, transcribed verbatim and analysed thematically with Nvivo 10 software. Results: Prevalence of early sex (first intercourse before age 16) was 58%, early marriage (union contracted before the age 18) was 30.0% and 80% of respondents did not consent to their marriage partner. About 42% of women have engaged in spousal communication on contraceptives. Also 24% experienced gender-based violence, 25% respondents' ever experienced unintended pregnancy and 44% experienced high fertility. The results from the qualitative study showed that persons who influence negative early Reproductive Health (RI-l) decisions of early sex, early marriage and consent of marriage partner were future partner, fathers of respondents and arranged marriages. Women who married before age 18 (early marriage) were also 3.27 times more likely to experience poor spousal communication relative to those who married between the age bracket of 26 - 36. Also women who had early sex and married early were significantly more likely to experience Gender Based Violence (GBV). The study further established a significant association between respondents experiencing early sex and GBV (p= 0.001). The odds of experiencing GBV were 2.65 times higher among women who first had sex before age 16 years (early sex) compared to those who first had sex between the ages of 16-25. Also of the respondents who had experienced unintended pregnancy, 72.5% (n=71) engaged in early sex (first intercourse before age 16). The odds of experiencing unintended pregnancy was 3.10 times higher among women who had sex before age 16 (early sex) compared to those who had sex between the ages of 16 to 25. Again, 39.8% (n=39) of the respondents who had unintended pregnancy married early. Also 81.6% (n=80) of the respondents who experienced unintended pregnancy did not consent to their marriage partner. Conclusion: The study found evidence linking negative early RH decisions of women to RH outcomes in the adult lives, suggesting that early RH choices affect later life reproductive health outcomes of respondents. These findings suggest that understanding women's current RH outcomes in the northern region requires looking closely at early life decisions which are likely to affect women later in life. Interventions in this direction can considerably improve women's health in the Northern region.
PhD - Public Health
Keywords: Early Reproductive Health; Child marriage; Ghana; Northern Region